Flowering variabilities in subtropical intertidal Zostera muelleri meadows of Australia - Lekammudiyanse, Manuja U.; Saunders, Megan I.; Flint, Nicole; Irving, Andrew; Jackson, Emma L. (Frontiers in Marine Science, 2023)
Flowering is an integral feature of the life history of seagrasses, and it contributes to the genetic diversity and resilience of meadows. There is some evidence that seagrass flowering is influenced by tidal depth; however, the effects of tidal exposure on the flowering variabilities in patchy intertidal meadows are largely unknown. In the present study, inter and intra-annual variability of flowering was examined using a line transect sampling method across two subtropical intertidal meadows (i.e., Lilley's Beach and Pelican Banks) of Zostera muelleri on Australia's east coast. Along each transect, the depth was measured using Leica Geosystems AGS14 RTK, and the plant cover was estimated using a standard scale.The duration of exposure at each depth was computed based on the tidal data and categorised exposure duration by hours. The abundance (i.e., the density of flowering shoots and density of spathes) and the ratio of flowering (i.e., flowering frequency) and morphology of flowering (i.e., the number of spathes per flowering shoot) were estimated along three 100 m fixed transects established perpendicular to the tide monthly in 2020 and 2021. Flowering started in July and extended for approximately six months, while peak flowering was observed in September-October in both sites. Generalised linear mixed-effect models showed that approximately 39% of the density of flowering shoots, 36% of the density of spathes and 28% of flowering frequency were explained by plant cover and exposure duration. Similar variation in the spathes per flowering shoot was explained by plant cover only (40%). The density of spathes during peak flowering months was significantly different among exposure categories (3-4 hrs and 5-6 hrs in Lilley's Beach and 5-6 hrs and 6-7 hr in Pelican Banks in 2021), where significantly different interannual variability was observed only between the same exposure categories in Pelican Banks. The study provides valuable insights on seed-based restoration projects, such as optimum seed harvesting times and the average amount of flowers that can be harvested, even though some inter-annual variations can be expected.